2017
DOI: 10.5958/2277-940x.2017.00157.7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Level of Women Dairy Farmers about Various Farming Practices in Border Area of Punjab

Abstract: Livestock farming is the most proficient occupation in India and women play a very significant role in livestock farming practices in the country. A study was conducted on 160 women dairy farmers of 4 border districts namely Gurdaspur, Amritsar, Taran-Taran and Ferozepur of Punjab to ascertain their knowledge level about various practices related to dairy farming. A pretested structured questionnaire comprising questions on management, nutrition, breeding, health etc. was developed and same was filled during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
3
4
2
Order By: Relevance
“…This might be because farm women in their middle years were deemed to be actively working and responsible for supporting their families through the cash earned from dairying operations. These were similar to the findings of Gulkari et al [10], Kaur et al [4], Yadav et al [5] and Bhunyan et al [11] who reported that more number of farm women belonged to middle age group in Anand district of Gujarat, Gurdaspur, Amritsar, Taran-Taran and Ferozepur districts of Punjab, Tumakuru district of Karnataka and Karnal district of Haryana, respectively.…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…This might be because farm women in their middle years were deemed to be actively working and responsible for supporting their families through the cash earned from dairying operations. These were similar to the findings of Gulkari et al [10], Kaur et al [4], Yadav et al [5] and Bhunyan et al [11] who reported that more number of farm women belonged to middle age group in Anand district of Gujarat, Gurdaspur, Amritsar, Taran-Taran and Ferozepur districts of Punjab, Tumakuru district of Karnataka and Karnal district of Haryana, respectively.…”
Section: Methodssupporting
confidence: 90%
“…Women play significant and crucial role in agricultural development and allied fields like dairy farming, Vermicomposting etc [2]. The socio-economic status and participation of women in dairying activities in different parts of the country were documented by various researchers [3][4][5][6][7]. Yet the crucial role of women in agriculture, allied occupations and household activities, on the other hand has been grossly underestimated and undervalued.…”
Section: Introductionmentioning
confidence: 99%
“…It was statistically similar in both the region. This figure was higher than that report of Kaur et al (2017). Results of the present study indicate that dairy farms of both regions were aware about breeding records keeping.…”
Section: Breeding Practicescontrasting
confidence: 87%
“…Animal husbandry and dairy is an important source of income and employment for millions of landless and play an important role in the socio-economic development in rural area [4].A study conducted by Kacker [5] also revealed that majority (85 percent ) of persons engaged in dairy production is women. Majority (68.75 percent) of border women in Punjab has medium knowledge level on various recommended dairy farming practices [6].…”
Section: Introductionmentioning
confidence: 99%